2020
DOI: 10.1002/mar.21407
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study on anthropomorphism and engagement with disembodied AIs and consumers' re‐use behavior

Abstract: The integration of artificial intelligence (AI) into the human race has gradually become a norm. AI entails technology assemblages such as machine learning, natural language processing, and reasoning. The influence of AI systems has intensified in consumers' daily lives. Many consumers have interacted with the notions of AI through advertisements or having personal experiences. Many consumers are curious about the use of AI. This paper reports three studies conducted to determine whether anthropomorphism (ANTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(92 citation statements)
references
References 90 publications
(143 reference statements)
6
85
1
Order By: Relevance
“…Another important result from Study 2 relates to the moderating role of perceived brand anthropomorphism in the relationship between self-disclosure and brand intimacy. This result complements the wide body of literature on brand anthropomorphism (Aggarwal & McGill, 2007;Puzakova & Aggarwal, 2018;Whang & Im, 2021) and preference for anthropomorphic agents (Moriuchi, 2021;Pozharliev et al, 2021). What we show is that, when applied to objects (e.g., branded products) or symbols (e.g., brands), self-disclosure of positive information-an act that is usually specific to human relationshipscan make the brand perceived as having human characteristics, which in turns affects the perception of people that they are intimate with the brand, a feeling that increases their WTB.…”
Section: Theoretical Contributionssupporting
confidence: 76%
“…Another important result from Study 2 relates to the moderating role of perceived brand anthropomorphism in the relationship between self-disclosure and brand intimacy. This result complements the wide body of literature on brand anthropomorphism (Aggarwal & McGill, 2007;Puzakova & Aggarwal, 2018;Whang & Im, 2021) and preference for anthropomorphic agents (Moriuchi, 2021;Pozharliev et al, 2021). What we show is that, when applied to objects (e.g., branded products) or symbols (e.g., brands), self-disclosure of positive information-an act that is usually specific to human relationshipscan make the brand perceived as having human characteristics, which in turns affects the perception of people that they are intimate with the brand, a feeling that increases their WTB.…”
Section: Theoretical Contributionssupporting
confidence: 76%
“…These links have been validated in the service literature (Kim & Stepchenkova, 2018; Ou & Verhoef, 2017) for negative emotions and in e‐commerce studies for trust (Gefen & Straub, 2003). However, the effect of trust on loyalty in a chatbot context, was not significant in other research (airline industry; Meyer‐Waarden et al, 2020 and personal intelligent agents; Moussawi et al, 2020; Pitardi et al, 2021). Therefore, it can be concluded that the results vary depending on the service context.…”
Section: Discussionmentioning
confidence: 75%
“…Specifically, when consumers feel in control and believe the technology is functional (easy to use), they will be more inclined to adopt the technology; consumers who do not feel in control, feel a certain dependency, and/or feel that the technology is challenging to use will be more resistant. What is often overlooked by these studies, however, is the dyadic relationship established between consumers and anthropomorphized technologies (Guzman, 2019; Kim & McGill, 2011; Moriuchi, 2021) and the psychological and social mediators therein. In the current study, consumers do not interact with VAs as products to be dominated or controlled, but rather as social entities attributed to human‐like characteristics, intentions, and behaviors (Moriuchi, 2021; Woods, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…What is often overlooked by these studies, however, is the dyadic relationship established between consumers and anthropomorphized technologies (Guzman, 2019; Kim & McGill, 2011; Moriuchi, 2021) and the psychological and social mediators therein. In the current study, consumers do not interact with VAs as products to be dominated or controlled, but rather as social entities attributed to human‐like characteristics, intentions, and behaviors (Moriuchi, 2021; Woods, 2018).…”
Section: Introductionmentioning
confidence: 99%